2008
DOI: 10.1096/fj.08-111013
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor ST18 regulates proapoptotic and proinflammatory gene expression in fibroblasts

Abstract: Suppression of tumorigenicity 18 (ST18) and the homologues neural zinc-finger protein-3 (NZF3) and myelin transcription factor 3 (Myt3) are transcription factors with unknown function. Previous studies have established that they repress transcription of a synthetic reporter construct consisting of the consensus sequence AAAGTTT linked to the thymidine kinase promoter. In addition, ST18 exhibits significantly reduced expression in breast cancer and breast cancer cell lines. We report here for the first time evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 33 publications
(36 reference statements)
3
67
1
2
Order By: Relevance
“…However, the authors did not specifically measure apoptosis in their system. Another publication demonstrated a proinflammatory role for ST18 in fibroblasts (6). In this study, siRNA-mediated knockdown of ST18 reduced TNF␣-induced apoptosis and proinflammatory gene expression, whereas its overexpression significantly enhanced apoptosis.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, the authors did not specifically measure apoptosis in their system. Another publication demonstrated a proinflammatory role for ST18 in fibroblasts (6). In this study, siRNA-mediated knockdown of ST18 reduced TNF␣-induced apoptosis and proinflammatory gene expression, whereas its overexpression significantly enhanced apoptosis.…”
Section: Discussionsupporting
confidence: 55%
“…Also, ectopic expression of ST18 reduced the tumorigenicity of MCF-7 cells (5), thereby suggesting a role for ST18 in tumor suppression. Furthermore, manipulation of ST18 expression in fibroblasts unraveled its potential proapoptotic and proinflammatory roles (6). ST18 expression was reported in the developing pancreas but its potential role in mature ␤-cells has never been investigated (4).…”
mentioning
confidence: 99%
“…24 The mutants demonstrated an upregulation of 18 transcription factors (Table 1D) as compared with controls. These transcription factors have been reported to participate in apoptosis, proliferation, differentiation and stress responses, [25][26][27][28][29] which is in line with studies reported by Garnett et al 24 where they showed an upregulation of 41 transcription factors, in pre diabetic ZDF islets, in comparison with Zucker-Fatty islets. 24 Accelerated aging has been an yet another well documented phenomenon in these mutants with their average life span shortened to 1.5 y as compared with 2.5-3 y seen in Controls and Leans.…”
Section: Resultssupporting
confidence: 83%
“…25 Supporting findings have shown that by silencing the activity of Tsc22d1, results in proliferation of hematopoetic precursors 26 while ST18 mediates tumor necrosis factor (TNFα) induced apoptosis and proinflammation in fibroblasts. 27 The role of RAX as an activator of PKR, has a diverse role in apoptosis induced stress is well reported. 28 An upregulation in the expression of CCAAT/enhancer binding proteins (CEBPA,CEBPE) by a fold of 2.73, 2.41 fold, have been linked to obesity in humans 29 and HMGA1 upregulated by 1.66 fold, is a key regulator of Insulin receptor gene expression, has been well associated with T2D in Chinese individuals.…”
Section: Resultsmentioning
confidence: 99%
“…NZF3 has been shown to be a breast cancer tumor suppressor gene (8) and has also been implicated in the regulation of mRNA levels of proapoptotic and proinflammatory genes in fibroblasts (9). The other paralog, MyT1L, has recently attracted substantial interest due to its ability to act in concert with two other transcription factors (Ascl1 and Brnd2) to transform mouse as well as human stem cells directly into functional neurons (10 -12).…”
mentioning
confidence: 99%